A Porcine Model for Urinary Tract Infection - Nielsen, Thomas Kastberg; Petersen, Nicky Anúel; Stærk, Kristian; Grønnemose, Rasmus Birkholm; Palarasah, Yaseelan; Nielsen, Lene Feldskov; Kolmos, Hans Jørn; Andersen, Thomas Emil; Lund, Lars (Frontiers in Microbiology, 2019)
Urinary tract infection (UTI) is the most common bacterial infectious disease with a high frequency of recurrence and the leading cause of septicemia. In vivo experimentation has contributed significantly to the present-day knowledge on urinary tract infection pathogenesis. This research has traditionally and almost exclusively been based on murine models of UTI. Conflicting results between UTI in mice and humans and increasing skepticism towards small rodent models in general warrant the need of novel large-animal infection models that better resemble the anatomy and physiology of humans, and thus better mimic the course of infection in humans. Here, we report, to our knowledge, the first large-animal model of cystitis. The model is based on pigs, and the protocol supports the establishment of persistent, non-ascending infection in this animal and is established without invasive surgical procedures, pain, and discomfort for the animal. The course of infection is monitored by cystoscopy, microscopy of bladder biopsies, and biochemical analysis of urine and blood samples. At termination, harvested whole bladders from infected pigs are analyzed for microbiological colonization using microscopy, histology, and viable bacterial counts. The model is a valuable tool in future studies of urinary tract infection pathogenesis and enables bridging of the current knowledge obtained from small-animal UTI models to UTI pathogenesis in humans.